Introduction: Towards a Better Understanding of Parliamentary Unity. Issue 2 (22nd February 2018) - Close, Caroline; Gherghina, Sergiu
Abstract: The study of parliamentary party unity has followed several lines of enquiry: describing the variation across political actors, contexts and time; comparing the multidimensional and dynamic aspects of parliamentary party unity; explaining it from a rational-institutional perspective with emphasis on macro-level arrangements and individual rational motivations. However, we know relatively little about how party organizations shape parliamentary party unity and this special section seeks to address this gap in the literature. This introductory article explains how the special section makes theoretical contributions to the concept of unity, provides alternative measurements and investigates several alternative determinants of unity.